Structural insights into the recognition of β(3) integrin cytoplasmic tail by the SH3 domain of Src kinase - Katyal, Priya (Blackwell Publishing Ltd, 2013)
Src kinase plays an important role in integrin signaling by regulating cytoskeletal organization and cell remodeling. Previous in vivo studies have revealed that the SH3 domain of c-Src kinase directly associates with the C-terminus of β(3) integrin cytoplasmic tail. Here, we explore this binding interface with a combination of different spectroscopic and computational methods. Chemical shift mapping, PRE, transferred NOE and CD data were used to obtain a docked model of the complex. This model suggests a different binding mode from the one proposed through previous studies wherein, the C-terminal end of β3 spans the region in between the RT and n-Src loops of SH3 domain. Furthermore, we show that tyrosine phosphorylation of β(3) prevents this interaction, supporting the notion of a constitutive interaction between β(3) integrin and Src kinase.